The Role of Accommodation in Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Accommodation is a dwelling; which tourists can use for temporary lodging. It is a place (such as a room or a suite in a hotel) wherein a tourist can stay and receive other services (dry-cleaning, room service etc.).